Debt accumulation of democracies facing low interest rate and election uncertainty. - Li, Yunong. (2011)
Intergenerational redistribution theory of fiscal policy and the tax-smoothing theory of fiscal policy are extremely valuable, as a matter of fact any positive model of fiscal policy begins with intergenerational distribution and tax smoothing as a benchmark. Yet neither of them manages to explain the observed large and persistent deficits in peacetime in 1980s and the cross-country differences for OECD economies. The recently observed continuous and significant debt accumulation of many European countries, Japan, and US also implies inconsistency between fiscal policies and tax smoothing theory as positive economic growth continued until the break of Global Financial Crisis (GFC). The paper, based previous literature develops a positive theory that could explain the effect of election uncertain, low interest, and voters' preference of public spend on debt accumulation.